2019
DOI: 10.1038/s41598-019-49980-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of thin films made from MoS2 nanoflakes and probed via statistical optothermal Raman method

Abstract: A deep understanding of the thermal properties of 2D materials is crucial to their implementation in electronic and optoelectronic devices. In this study, we investigated the macroscopic in-plane thermal conductivity (κ) and thermal interface conductance (g) of large-area (mm2) thin film made from MoS2 nanoflakes via liquid exfoliation and deposited on Si/SiO2 substrate. We found κ and g to be 1.5 W/mK and 0.23 MW/m2K, respectively. These values are much lower than those of single flakes. This difference shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…We have found the value of g ∼ 1.264 ± 0.128 MW m –2 K –1 and k s ∼ 42 ± 8 W m –1 K –1 by solving MATLAB program. In literature, it has been observed that the mono- or multilayer MoS 2 shows the values of interfacial thermal conductance “ g ” from 0.1 to 14 MW m –2 K –1 , and low “ g ” values are found by the Raman optical thermometry method compared to other methods like the electrical thermometry method. ,, In the present work, we found the value of “ g ” around 1.264 ± 0.128 MW m –2 K –1 for triangular bilayer MoS 2 over the SiO 2 /Si substrate. The interfacial coupling may be affected by lattice mismatch between MoS 2 and substrate .…”
Section: Resultssupporting
confidence: 44%
“…We have found the value of g ∼ 1.264 ± 0.128 MW m –2 K –1 and k s ∼ 42 ± 8 W m –1 K –1 by solving MATLAB program. In literature, it has been observed that the mono- or multilayer MoS 2 shows the values of interfacial thermal conductance “ g ” from 0.1 to 14 MW m –2 K –1 , and low “ g ” values are found by the Raman optical thermometry method compared to other methods like the electrical thermometry method. ,, In the present work, we found the value of “ g ” around 1.264 ± 0.128 MW m –2 K –1 for triangular bilayer MoS 2 over the SiO 2 /Si substrate. The interfacial coupling may be affected by lattice mismatch between MoS 2 and substrate .…”
Section: Resultssupporting
confidence: 44%
“…Now we turn our attention toward the estimation of thermal conductivity and thermal interface conductance of WS 2 thin film on SiO 2 substrate. To do so, we used the well-established optothermal Raman technique, which studies phonon response to global heating and local laser heating. , The details of the experimental and theoretical basis of this method can be found in our previous works and Supporting Information. , In brief, during the Raman experiment, we can increase the temperature of the sample by laser illumination. The temperature increase is dependent on power input and distribution.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, we point out that results presented here are part of a larger trend as similar results were shown for graphene and MoS 2 , where the films produced from nanoflakes have also at least 1 order of magnitude smaller thermal conductivity than their monocrystalline bulk and monolayer counterparts (see Table ). , Such results can be useful in managing the heat in future applications of thin film and bring new insights into proper device optimization and design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 Some recent papers report thermal conductivities below 1 W/m•K in polycrystalline thin films with a record lowest value of 0.27 W/m•K reported on polycrystalline films with perfect controlled grain orienta-tion. 38,59,60 Experimentally, the out-of-plane thermal conductivity of bulk MoS 2 at 300 K is reported with values in a common range of 2.2−6.1 W/m•K and the lowest value of 1.05 W/m•K has been reported in restacked compounds with a similar 2H phase in the room temperature range. 28,49,61 This current state of the art ranks our samples in the lowest range of MoS 2 thermal conductivity ever reported.…”
Section: Electrical Transport Propertiesmentioning
confidence: 99%